O processo de responsabilização da Administração Pública e sua relação a Atenção Primária à Saúde na região do ABC - Bassi, Marcos Sidnei (2012)
This dissertation analyses the relation between the accountability of the Public Administration, particularly the actions resulting from Social Control -, and the quality of the services of the APS (Primary Heath Attention), in five cities from the ABC region in São Paulo, Brazil. The subjects investigated were users from the UBS services (Basic Health Unities) who agreed to answer the PCA Tool (Primary Care Assessment Tool). The resulting data were compared with the analysis of the reports from the Municipal Councils for Health of each city. Multivariate Analysis and PLS (Partial Least Square) were used to check relationships